2008
DOI: 10.1002/chem.200701447
|View full text |Cite
|
Sign up to set email alerts
|

Selective Gas Adsorption and Unique Structural Topology of a Highly Stable Guest‐Free Zeolite‐Type MOF Material with N‐rich Chiral Open Channels

Abstract: A new multifunctional di-topic tetrazolate-based ligand, 2,3-di-1H-tetrazol-5-ylpyrazine (H(2)dtp) has been designed and synthesized. The solvothermal reaction of this ligand with ZnCl(2) gave a robust guest-free three-dimensional zeolite-like chiral metal-organic framework (MOF) complex, [Zn(dtp)], which crystallized in chiral space group P6(1) and possessed chiral open channels with nitrogen-rich walls and the diameter of approximately 4.1 A. This framework presents a unique uniform etd (8,3) topology, is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
135
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(135 citation statements)
references
References 88 publications
0
135
0
Order By: Relevance
“…Nevertheless, some reports have also emerged describing the selective adsorption of CO 2 over other gases (i.e., N 2 , CH 4 , O 2 , C 2 H 2 or CO), some of which even comprise binary (e.g., CO 2 /CO, CO 2 /N 2 or CO 2 /CH 4 ) and ternary (CO 2 /N 2 /CH 4 , CO 2 /N 2 /H 2 O or CO 2 /N 2 /O 2 ) gas mixtures. 116,117,[125][126][127][128][129][130][131][132] Wang et al reported two porous zeolite-type imidazolate frameworks, coined as ZIF-95 and ZIF-100, possessing complex cages with 264 vertices and constructed from about 7524 atoms. 125 After breakthrough experiments it was discovered that these ZIFs have a great ability to selective adsorb CO 2 from mixtures of CO 2 /CH 4 , CO 2 /CO and CO 2 /N 2 (50:50 v/v).…”
Section: -Co 2 Capturementioning
confidence: 99%
“…Nevertheless, some reports have also emerged describing the selective adsorption of CO 2 over other gases (i.e., N 2 , CH 4 , O 2 , C 2 H 2 or CO), some of which even comprise binary (e.g., CO 2 /CO, CO 2 /N 2 or CO 2 /CH 4 ) and ternary (CO 2 /N 2 /CH 4 , CO 2 /N 2 /H 2 O or CO 2 /N 2 /O 2 ) gas mixtures. 116,117,[125][126][127][128][129][130][131][132] Wang et al reported two porous zeolite-type imidazolate frameworks, coined as ZIF-95 and ZIF-100, possessing complex cages with 264 vertices and constructed from about 7524 atoms. 125 After breakthrough experiments it was discovered that these ZIFs have a great ability to selective adsorb CO 2 from mixtures of CO 2 /CH 4 , CO 2 /CO and CO 2 /N 2 (50:50 v/v).…”
Section: -Co 2 Capturementioning
confidence: 99%
“…One such barrier is the lack of lightweight, high-density, low-cost hydrogen storage technologies. [1,2] Over the past decades, many advanced materials including complex metal hydrides, [3] chemical hydrides, [4,5] and metal-organic frameworks [6][7][8] have been explored as potential on-board hydrogen storage candidates. In particular, the lightweight complex metal hydrides (MAlH 4 and MBH 4 , M: alkali metal) enhanced by 3d-transition metal (TM) compounds offer a promising opportunity as solid-state hydrogen storage media for transportation applications due to Bogdanovic and Schwickardis breakthrough discovery with Ti-doped NaAlH 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The Bader charges of the dihydrogen complex are listed in Table 1 together with those of TiAl 3 H 12 and TiAl 3 H 10 A C H T U N G T R E N N U N G (7,8), the product of losing the dihydrogen. The projected LDOS of Ti, A1 1 , and Al 2 as well as the two H atoms are shown in Figure 6.…”
mentioning
confidence: 99%
“…CO 2 isotherms were collected at 196 K ( Figure S13). The isotherms show rapid uptake of CO 2 and reach saturation arount 100 Torr which allows calculation of the pore volumes of the MOFs (Table 1). The results showed slightly higher values compared to those from the N 2 sorption data at 77 K. However, the results for both MOFs are very similar and follow the same trend of WUF-2 having a slightly larger pore volume.…”
Section: Gas Sorption Studiesmentioning
confidence: 99%